Introduction to Biosemiotics The New Biological Synthesis - Barbieri, Marcello (Springer Netherlands : Imprint: Springer, 2007)
This book is addressed to students, researchers and academics who have barely heard of the emerging young science of Biosemiotics, and who want to know more about it. Written by many of the field's major contributors, it provides a highly qualified introduction to Biosemiotics and illustrates the most recent views in its background and development. Combining research approaches from biology, philosophy and linguistics, the field of Biosemiotics proposes that animals, plants and single cells all engage in semiosis - the conversion of objective signals into conventional signs. This has important implications and applications for issues ranging from natural selection to animal behavior and human psychology, leaving biosemiotics at the cutting edge of the research on the fundamentals of life. Drawing on an international expertise, the book details the history and study of biosemiotics, and provides a state-of-the-art summary of the current work in this new field. And, with relevance to a wide range of disciplines - from linguistics and semiotics to evolutionary phenomena and the philosophy of biology - the book provides an important text for both students and established researchers, while marking a vital step in the evolution of a new biological paradigm. Marcello Barbieri is University Professor of Embryology at the University of Ferrara, Italy, President of the Italian Association for Theoretical Biology and Editor-in-Chief of the Journal of Biosemiotics.